Theoretical investigation of environmental development pathways in the road transport sector in the European Region - Szendrő, Gabor; Török, Ádám (Transport, 2014)
With the omnipresent influence of mankind around the world, controlling resource use and pollution are key factors in the progress toward sustainability in all sectors. These considerations appear in international and European policies, but there remains a need to make these policies suited to local conditions. This article aims to present a method of analysis for the transport sector that could prove useful for identifying the similarities and differences in the current state and historical development of transport systems in EU Member States. First Published Online: 25 Mar 2014